Representation of Religious Moderation Values in Arabic Language Textbooks of Madrasah Aliyah: Insights from the Ministry of Religious Affairs of the Republic of Indonesia - Fikri, Ahmad Futunul; Khofifah, Khofifah; Fauziah, Fauziah; Muhajir, Muhajir (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Although much research has been conducted on the representation of religious moderation values in textbooks, there are still few who study it from the perspective of Arabic textbooks. Thus, this research aims to examine the representation of religious moderation values in the Madrasah Aliyah Arabic language textbook for class XI: insights from the Ministry of Religion of the Republic of Indonesia. This research uses a library research design with a qualitative approach. The research results show that the content of the Arabic textbook consists of 6 chapters covering shopping, health, travel, Hajj and Umrah, information and communication technology, and religion in Indonesia. The values of religious moderation in the class XI Arabic textbook are on page 57 with the theme "Umrah with my family" on listening skills and page 59 on reading skills. Tolerance is found on page 90 of the theme "religion in Indonesia" in reading skills and page 99 in speaking skills. Anti-violence is found on page 31 of the theme "health" in speaking skills and page 63 of the theme "Hajj and Umrah" in grammar rules skills. Accommodating to local culture is found on page 38 of the "travel" theme in reading skills. This textbook shows that the Madrasah Aliyah Arabic language learning materials for class XI represent the values of religious moderation namely national commitment, tolerance, non-violence, accommodating to local culture as shown through illustrative images, Not only is the material presented but elements of Indonesian cultural values are also depicted in the textbook. So Arabic is not just learning the language but also learning the cultural values in textbooks. Analysis of Arabic textbooks on moral issues, other Arabic books using thematic context analysis research and morphological analysis can be used for further research.